Pengaruh Motivasi Kerja, Kompetensi Sumber Daya Manusia dan Disiplin Kerja terhadap Kinerja Pegawai - Mawar Khairunnisa; Yupiter Gulo (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
The purpose of this study is to analyze the effect of work motivation, human resource competence, and work discipline on employee performance at PT Pelabuhan Indonesia (Persero) Regional 2 Tanjung Priok. Sampling using non-probability sampling technique with a total sample used as many as 74 respondents. The study was analyzed using a statistical software program. Multiple linear regression is used in this study as the data analysis method. The results of this study showed that the work motivation had no effect on employee performance while human resource competence, and work discipline had an effect on employee performance.